Human Health, Ecosystem Quality, and Resource Scarcity Burdens Inflicted by Livestock Production Across Chinese Regions - Yixuan Shao; Qilin Cao; Junnian Song; Jiahao Xing; You Wu; Cheng Sun; Pan He; Wei Yang (Earth's Future)
Abstract Surge in global population and shift toward animal‐based diets have accelerated expansion of livestock production, posing various environmental challenges. It requires inventorying localized, activity‐specific, and indicator‐extended multidimensional eco‐environmental burdens and revealing their transfers within interregional trade to inform holistic livestock production management from both production and consumption sides. Herein, we construct a life cycle framework covering multiple livestock species, feeding regimes, and activities to evaluate nine environmental impacts ending up as human health, ecosystem quality and resource scarcity burdens in Chinese provincial regions. Multi‐regional input‐output analysis is then conducted to trace transfers of these burdens embedded within trade associated with livestock production. Results indicate that fine particulate matter formation (mainly by livestock housing) and climate change (mainly by enteric fermentation) contribute greater than 60% and 30% to health burdens. Besides for health burdens, for ecosystem burdens primarily caused by housing, and resource burdens mainly aggravated by high on‐farm energy use, poultry results in the highest level. The main production regions Shandong, Henan and Sichuan lead from perspectives of both production and consumption‐based burdens. Whereas regions with the largest export (Inner Mongolia, 3.87 × 104 DALY for health burdens) or import (Guangdong, 3.92 × 104 DALY for health burdens) do not necessarily bear greatest burdens. This work provides policy instructions in mitigating various eco‐environmental burdens imposed by livestock production and promoting sustainable agricultural practices.